Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 950 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Potos flavus (Schreber, 1774)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 950 records from 62 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007889-160526112335914/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences